Enhanced transdermal peptide delivery and stability by lipid conjugation: Epidermal permeation, stereoselectivity and mechanistic insights - Namjoshi, S.; Toth, I.; Blanchfield, J.; Trotter, N.; Mancera, Ricardo; Benson, Heather (AAPS, 2014)
Purpose: Efficient delivery of therapeutic peptides to the skin will facilitate better outcomes in dermatology. The tetrapeptide AAPV, an elastase inhibitor with potential utility in the management of psoriasis was coupled to short chain lipoamino acids (Laa: C6-C10) to enhance the peptide permeation into and through human epidermis.Methods: AAPV was conjugated to Laas by solid phase synthesis. Peptide stability, skin distribution and permeation, elastase activity and surface activity were determined.Results: Laas increased peptide permeation into the skin. The permeation lag time and amount of peptide remaining in the skin increased with the carbon chain length of the Laa conjugate. We also demonstrated stereoselective permeation enhancement in favour of the D-diastereomer. Importantly, the elastase inhibition activity of the peptide was largely retained after coupling to the Laa conjugates, showing potential therapeutic utility. The Laa-peptide structures were shown to be surface active, suggesting that this surfactant-like activity coupled with enhanced lipophilicity may contribute to their interaction with and permeation through the lipid domains of the stratum corneum.Conclusions: This study suggests that the Laa conjugation approach may be useful for enhancing the permeation of moderately sized peptide drugs with potential application in the treatment of skin disorders.